Cholera Toxin Induces Sustained Hyperexcitability in Myenteric, but Not Submucosal, AH Neurons in Guinea Pig Jejunum - Koussoulas, Katerina; Gwynne, Rachel M.; Foong, Jaime P. P.; Bornstein, Joel C. (Frontiers in Physiology, 2017)
Background & Aims: Cholera toxin (CT)-induced hypersecretion requires activation of secretomotor pathways in the enteric nervous system (ENS). AH neurons, which have been identified as a population of intrinsic sensory neurons, are a source of excitatory input to the secretomotor pathways. We therefore examined effects of CT in the intestinal lumen on myenteric and submucosal AH neurons. Methods: Isolated segments of guinea pig jejunum were incubated for 90 min with saline plus CT (12.5 µg/ml) or CT + neurotransmitter antagonist, or CT + TTX in their lumen. After washing CT away, submucosal or myenteric plexus preparations were dissected keeping circumferentially adjacent mucosa intact. Submucosal AH neurons were impaled adjacent to intact mucosa and myenteric AH neurons were impaled adjacent to, more than 5 mm from, and in the absence of intact mucosa. Neuronal excitability was monitored by injecting 500 ms current pulses through the recording electrode. Results: After CT pre-treatment, excitability of myenteric AH neurons adjacent to intact mucosa (n=29) was greater than that of control neurons (n=24), but submucosal AH neurons (n=33, control n=27) were unaffected. CT also induced excitability increases in myenteric AH neurons impaled distant from the mucosa (n=6) or in its absence (n=5). Coincubation with tetrodotoxin or SR142801 (NK3 receptor antagonist), but not SR140333 (NK1 antagonist) or granisetron (5-HT3 receptor antagonist) prevented the increased excitability induced by CT. Increased excitability was associated with a reduction in the characteristic AHP and an increase in the ADP of these neurons, but not a change in the hyperpolarisation-activated inward current in Ih. Conclusions: CT increases excitability of myenteric, but not submucosal, AH neurons. This is neurally mediated and depends on NK3, but not 5-HT3 receptors. Therefore, CT may act to amplify the secretomotor response to CT via an increase in the activity of the afferent limb of the enteric reflex circuitry.